2017
DOI: 10.3389/fnmol.2017.00236
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advancements in the Regeneration of Auditory Hair Cells and Hearing Restoration

Abstract: Neurosensory responses of hearing and balance are mediated by receptors in specialized neuroepithelial sensory cells. Any disruption of the biochemical and molecular pathways that facilitate these responses can result in severe deficits, including hearing loss and vestibular dysfunction. Hearing is affected by both environmental and genetic factors, with impairment of auditory function being the most common neurosensory disorder affecting 1 in 500 newborns, as well as having an impact on the majority of elderl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 157 publications
0
38
0
1
Order By: Relevance
“…Hearing loss is a serious global morbidity that affects 360 million people worldwide [1], and this neurological disability impacts both the physical and mental health of patients [2]. Recent research has revealed several mechanisms and molecules that contribute to hearing loss, such as oxidative stress and apoptotic cell death [3].…”
Section: Introductionmentioning
confidence: 99%
“…Hearing loss is a serious global morbidity that affects 360 million people worldwide [1], and this neurological disability impacts both the physical and mental health of patients [2]. Recent research has revealed several mechanisms and molecules that contribute to hearing loss, such as oxidative stress and apoptotic cell death [3].…”
Section: Introductionmentioning
confidence: 99%
“…The organ of Corti is a sensory structure that detects sound in mammals possessing dual sensory systems with inner and outer hair cells which are important to hearing ability [Lim, 1986]. Noise exposure may cause harm to the organ of Corti resulting in irreversible structural cellular damage to the hair cells and supporting cells [Mittal et al, 2017;Moser and Starr, 2016]. SIK3 is important during the early stages of development in hair cells or stereocilia, and a maintenance function of SIK3 in spiral ganglion was found in mice [Wolber et al, 2014].…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies suggest that IGF1 promotes inner ear neuronal development by supporting neurogenesis, differentiation and proliferation of neuronal progenitor cells (Aburto, Magarinos, Leon, Varela‐Nieto, & Sanchez‐Calderon, ; Ayaso, Nolan, & Byrnes, ; Varela‐Nieto, Murillo‐Cuesta, Rosa, Lassatetta, & Contreras, ; Tafra et al, ). IGF1 may also promote cochlear hair cell survival by limiting the degree of cochlear inflammation and oxidative stress and down‐regulating pro‐apoptotic gene expression (Mittal et al, ; Yamahara et al, ; Yang et al, ).…”
Section: Hormonal Factorsmentioning
confidence: 99%
“…Expression of IGF1 is highest during late cochlear development, declines significantly after birth; although IGF‐1 expression is maintained throughout life, circulating bioactive IGF‐1 levels decline with age, leading to increased inflammation and failure of intracellular renewal mechanisms (Mittal et al, ; Murillo‐Cuesta, Rodríguez‐de la Rosa, Cediel, Lassaletta, & Varela‐Nieto, ; Vestergaard et al, ). IGF1 has been detected throughout the mouse inner ear, including the spiral ganglion, spiral ligament, stria vascularis, hair cells, and in vestibular tissues (de la Rosa et al, ; Degerman et al, ; Riva, Donadieu, Magnan, & Lavieille, ).…”
Section: Hormonal Factorsmentioning
confidence: 99%